Ongoing Issues in Water Distribution Systems and Solutions to Address Them - Gallant, Richard; Bloetscher, Frederick; Meeroff, Daniel E. (European Journal of Applied Sciences, 2022)
The goal of water utilities is to provide sufficient quantities of high quality water that does not pose a public health concern to its customers. For the most part, publicly owned water systems comply with all regulations on a consistent basis, but the backlog of infrastructure needs means that longer term, compliance may be an issue. Operational issues like biofilm management is particularly tricky for utilities to deal with. The results herein indicate that biofilm formation potential can be predicted with discriminant analysis and linear regression if sufficient data is obtained. The correct data is important. The data also indicates that utilities at risk for biofilms should include measures to reduce biofilms in their regularly scheduled maintenance. In trying to address competing issues in a cost limited environment can create internal conflicts, where implementing one solution creates a new problem. The desire to save money can also compromise compliance and endanger public health.